2018
DOI: 10.30566/2600-8254.2018.2.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Model to Discover the Effect of Religiosity and Spirituality on Organizational Performance

Abstract: The purpose of this paper is to develop a model to explore the impact of religiosity and spirituality on performance organizations through organizational commitment. This study adopted Religiosity and Spirituality as independent variables, organizational commitment as mediating and Performance as a dependent variable. The study is based on conceptual research. Through this study, a model will be proposed to find out the relationship among religiosity, spirituality, organizational commitment and organizational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Most frequently, spirituality is regarded as fundamentally personal, although it can exist or manifest in groups and organizations (Woods, 2007). From this viewpoint, a religious spirituality is an entity that has grown and developed over time through the spiritual experiences of one or more founders, providing the basis for leadership based on the religions and practices (Peltonen, 2017;Rouhoma, Dhar, Ali, & Osman, 2018).…”
Section: Spiritual Leadership and Workplace Spiritualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Most frequently, spirituality is regarded as fundamentally personal, although it can exist or manifest in groups and organizations (Woods, 2007). From this viewpoint, a religious spirituality is an entity that has grown and developed over time through the spiritual experiences of one or more founders, providing the basis for leadership based on the religions and practices (Peltonen, 2017;Rouhoma, Dhar, Ali, & Osman, 2018).…”
Section: Spiritual Leadership and Workplace Spiritualitymentioning
confidence: 99%
“…Spiritual leadership and related research have shown that it predicts various important individual and organizational outcomes in multiple countries and cultures (Fry & Cohen, 2009). These include being positively related to organizational commitment (Rouhoma et al, 2018), job satisfaction (Sani et al, 2016), altruism, awareness, self-career management (Lewis & Geroy, 2000), job participation (Seong & Hong, 2018), retention (Armstrong-Stassen & Schlosser, 2011), life satisfaction and work unit productivity (Bene el, 2005;Chen et al, 2013;Fry & Nisiewicz, 2013;Hunsaker, 2019).…”
Section: Workplace Spirituality and Productivitymentioning
confidence: 99%
“…Evaluating the financial performance of a company is basically evaluating the impact of the strategies of a firm regarding financial matters. The results of such decisions are evident in the evaluation of the worth of a company or a business enterprise through assessment of the return on investment and return on assets (Dhar, 2019a,b;Dhar et al, 2017Dhar et al, , 2018Saeed et al, 2017;Rouhoma et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some of the variables that have an impact on performance are work stress, workload and religiosity. Several factors influence employee performance and how employees engage with their work and organizations (Brien et al, 2021;Rouhomaa et al, 2018), including religiosity and workload, which are viewed as the primary drivers of engagement leading to engagement (Mathew et al, 2019;Nisar & Rasheed, 2020). Aside from workload, there is still literature that discusses the significance of religiosity in influencing employees' work-related attitudes and behaviors (Abbas et al, 2020;Rouhomaa et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several factors influence employee performance and how employees engage with their work and organizations (Brien et al, 2021;Rouhomaa et al, 2018), including religiosity and workload, which are viewed as the primary drivers of engagement leading to engagement (Mathew et al, 2019;Nisar & Rasheed, 2020). Aside from workload, there is still literature that discusses the significance of religiosity in influencing employees' work-related attitudes and behaviors (Abbas et al, 2020;Rouhomaa et al, 2018). Furthermore, the literature has suggested that religiosity influences employee engagement (Villani International Journal of Social Science andBusiness, Vol.…”
Section: Introductionmentioning
confidence: 99%